Validation on Utrecht Work Engagement Scale: Multisample and Multi Sectors Analysis - Iwan Sidharta (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2018)
Research on work engagement has proven by previous studies that showed constructive, positive behaviors related to work. Several studies used the Utrecht Work Engagement Scale (UWES) instrument, but evidence of instrument construct validity is only available in some countries. This study investigates the validity of UWES constructs using a multisample in several sectors in the Greater Bandung Region, Indonesia. The approach to testing validity uses confirmatory factor analysis with the Lisrel 8.8 program tool. The results of the study showed that version 17 of the Utrecht Work Engagement Scale (UWES) instrument was valid and realistic in a multisample in several industrial sectors in the Greater Bandung Region, Indonesia. The research implications can recommend the use of version 17 of the Utrecht Work Engagement Scale (UWES) instrument to measure Work Engagement at the individual level in the organization.